Giant Cell Tumor: A Rare Condition in the Immature Skeleton—A Retrospective Study of Symptoms, Treatment, and Outcome in 16 Children. (23rd November 2016) - Strøm, Thale M. Asp; Skeie, Anette Torød; Lobmaier, Ingvild Koren; Zaikova, Olga
Abstract : Background . Pediatric giant cell tumor (GCT) of bone is rare and the course of the disease in the immature skeleton is sparsely described. We performed a retrospective study addressing symptoms, treatment, and outcome in children with GCT. Methods . Review of medical records and images of patients with GCT. Patients were detected from our hospital prospective database and those with open epiphyseal cartilages were included. Results . 16 children (75% girls) from 6 to 15 years old were identified. Eight lesions (50%) were in long bones and 4 (25%) in flat bones. One lesion appeared to be purely epiphyseal. All patients had pain as the initial symptom. Local recurrence developed in 2 patients. 14 of 16 patients returned to normal activity with no sequelae. One patient developed anisomelia after surgery. Conclusions . The biological tumor behavior in children does not seem to differ from what is reported in adults. Lesions in flat bones are very unusual, but our data alone do not provide enough evidence to conclude that this is more common in the immature skeleton. Literature review showed only one previous case report describing a purely epiphyseal GCT. Intralesional curettage is appropriate treatment and gives good functional results with acceptable recurrence rates.